AN ANALYSIS ON REQUEST STRATEGIES USED BY THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Kurnia, Auziq; Purwanti, Indah Tri; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract: This research aims to find what types of request strategies are used bythe sixth-semester students in the English Study Program in Universitas Riau. Thisresearch is a descriptive qualitative approach. The samples of this research are thesixth-semester students of the English Study Program Universitas Riau. The totalnumber of students is 114 students. They are divided into 3 classes. One of the classeswere selected using Cluster Random Sampling (CRS). The number of sample is 38students. Data collection technique in this research was discourse completion task(DCT). The analysis of data was conducted by sending a Google form to the sixth-semester students of the English Study Program. In this study, the researcher employs aqualitative data analysis methodology. The result shows that the respondents moreprefer to use conventionally indirect query preparatory strategy. And some of thepercentage strategies used are as follows; direct explicit performatives withoccurrences (0.8%), want statements with occurrences (2.3%), conventionally indirectquery preparatory with occurrences (94.6%), and non-conventionally indirect mild hint(2.0%).Key Words: Request Strategies, Direct Strategies, conventionally Indirect,Non-conventionally Indirect, Speech Act